1981
DOI: 10.1177/000331978103201105
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Findings in Systemic Necrotizing Vasculitis

Abstract: Angiographic studies were carried out on 21 patients with systemic necrotizing vasculitis. Four basic arterial anomalies were found: (1) saccular microaneurysms appeared in 62% of the patients (2) arterial thrombosis was seen in 81% of patients; (3) arterial stenosis occurred in 81%; and (4) lumen irregularities occurred in 90%. Alterations in the renal vascular flow were also observed in accordance with changes in the cortical medullary differentiation, heterogeneous nephrogram, and prolonged washout. Two pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Serum complement components were normal and serologic tests for systemic lupus erythematosus (SLE), HBV infection, circulating immune complexes, cryoimmunoglobulins and antiglomerular basement membrane antibodies were nega tive. In the absence of drug addiction, allergy history, eosinophilia or disorders like SLE or atrial mixoma, the finding of multiple intraparenchymal saccular aneu rysms demonstrable by renal angiography is virtually diagnostic of classic PAN [15,16]. In our patient, the glomerular lesions consisted in necrotizing glomerulon ephritis, an uncommon histological entity responsible for only 5% of all glomérulonéphrites according to a recent report [17], but the most frequent histological finding in patients with classic PAN.…”
Section: Discussionmentioning
confidence: 53%
“…Serum complement components were normal and serologic tests for systemic lupus erythematosus (SLE), HBV infection, circulating immune complexes, cryoimmunoglobulins and antiglomerular basement membrane antibodies were nega tive. In the absence of drug addiction, allergy history, eosinophilia or disorders like SLE or atrial mixoma, the finding of multiple intraparenchymal saccular aneu rysms demonstrable by renal angiography is virtually diagnostic of classic PAN [15,16]. In our patient, the glomerular lesions consisted in necrotizing glomerulon ephritis, an uncommon histological entity responsible for only 5% of all glomérulonéphrites according to a recent report [17], but the most frequent histological finding in patients with classic PAN.…”
Section: Discussionmentioning
confidence: 53%
“…It has been suggested that the angiographic demonstration of aneurysms in PAN might identify a group of PAN patients with greater disease severity [20][21][22]. However, not all patients suffering from histologically verified PAN have angiographically demonstratable aneurysms [15]. Studies on angiographic changes in patients with PAN have been scarce, and controversy persists over what produces the regression of microaneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple colonic ulcers often occur in PAN, and digestive organ lesions are important indicators of the prognosis. The diagnostic indicators of abnormal abdominal angiography findings due to PAN have been established [14,15], and included in the ACR classification criteria [7], but their improvement has not been closely described.…”
Section: Introductionmentioning
confidence: 99%
“…10 Other, less specific, findings on angiography include arterial stenosis, thrombosis, and occlusion. 11 The sensitivity and specificity of angiography in the diagnosis of PAN is reported to be 89% and 90%, respectively. 10 Arterial occlusions may result in end-organ damage from infarction and are often first identified on CT scan during initial workup.…”
Section: Discussionmentioning
confidence: 99%